CoNeT Mobile Laboratory for Ethernet Based I/O Systems in Industrial Applications - Ucun, Levent; Akbati, Onur; Cansever, Galip (IEEE, 2012)
This paper studies Ethernet based I/O systems in industrial applications. This study is involved in CoNeT, the European Union funded project, which stands for Cooperative Network Training. The project aims at training of automation engineers, maintenance engineers, process workers and students both graduate and undergraduate in modern wired and wireless industrial network technology applied to control operations and automated solutions. Seven modules dealing with different subjects about industrial automation have been designed in the concept of the project. This study has been carried out to design the first module which is about training in Ethernet based I/O systems. Mobile laboratory involving different industrial communication devices from different automation manufacturers has been founded and industrial application-oriented experiments have been designed to be carried out in the mobile laboratory.
Keywords: Industrial automation training; industrial network systems; Ethernet based I/O systems; REAL-TIME; Automation & Control Systems; Computer Science